Effects of Dapagliflozin on EChOcardiographic Measures of CarDiac StructurE and Function in Patients with Chronic Kidney Disease: The DECODE-CKD Trial. Issue 2 (18th February 2023) - Bartholdy, Katja Vu; Johansen, Niklas Dyrby; Landler, Nino; Skaarup, Kristoffer Grundtvig; Jensen, Jesper; Bressendorff, Iain; Schou, Morten; Christensen, Jacob; Feldt-Rasmussen, Bo; Vaduganathan, Muthiah; Solomon, Scott; Haynes, Richard; et al.
Abstract : Abstract : Key Points: SGLT2 inhibitors (SGLT2i) exert cardioprotective effects in patients with CKD through unknown mechanisms. DECODE-CKD is the first randomized controlled trial (RCT) to evaluate the effects of SGLT2i on cardiac structure and function in patients with CKD. Background: SGLT2 inhibitors, originally developed as glucose-lowering agents for treatment of type 2 diabetes, have been shown to have cardio- and kidney-protective effects among CKD patients with and without diabetes. However, the mechanisms remain largely unknown. Methods: Dapagliflozin on EChOcardiographic Measures of CarDiac StructurE and Function in Patients with Chronic Kidney Disease (DECODE-CKD) is an investigator-initiated, prospective, single-center, randomized, placebo-controlled trial evaluating the effects of 6 months of treatment with 10 mg of dapagliflozin compared with placebo on cardiac structure and function in 222 adults with CKD. Results: The primary objective was to assess whether dapagliflozin improves left ventricular mass index. Secondary and exploratory end points include changes in cardiac and kidney markers, quality of life, depressive symptoms, and cognitive function. Conclusions: This is the first study to address the effects of SGLT2 inhibitors on cardiac structure and function in patients with CKD. The results will provide valuable insights into the mechanisms underlying the cardioprotective benefits of SGLT2 inhibitors in patients with CKD. Clinical Trial registry name and registration number: NCT05359263